Locating the government: Capital cities and civil conflict. (October 2017) - Potter, Alan
The location of the national capital is frequently contentious in domestic politics. Almost 30% of countries house their capitals outside of their largest city and 11 countries have relocated their capitals since 1960. This paper argues that locating the capital outside of the largest urban center may reduce civil conflict by limiting the ability of any single faction to dominate the government. When the government is less afraid of large urban populations in the capital, it is better able to appease multiple factions. Cross-national evidence supports this argument in that locating the capital outside of a major city is associated with a significant reduction in both violent and non-violent civil conflict.